Verification of Concurrent Object-Oriented Programs - Leino, Rustan; Zurich), Peter Müller, (ETH (Microsoft Research, 2009)
Software engineering research Goal Better build, maintain, and understand programs How? Specifications Tools, tools, tools Program semantics Verification-condition generation, symbolic execution, model checking, abstract interpretation, fuzzing, test generation Satisfiability Modulo Theories (SMT)